2020
DOI: 10.1155/2020/8847087
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Method of Wear for Volute Casing of a Centrifugal Slurry Pump

Abstract: Volute wall wear situations directly affect a long time safe operation for the centrifugal slurry pump unit and the whole system. In the present study, internal flow field is numerically investigated in a solid-liquid centrifugal pump, and the volute wall wear caused by the solid-liquid two-phase flow is predicted with wear equation. A systematic analysis on the wear mechanism of the centrifugal pump volute wall is carried out deeply, including the volute wall wear region, wear rate, and the relationship among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Wu et al [18] studied the influence of unstable flow characteristics on pump performance and found that relatively high-speed particles would accelerate blade tail wear. Shi et al [19] studied the internal flow field in a solid-liquid centrifugal pump and proposed the wear equation to predict the volute wear caused by solid-liquid two-phase flow. The experimental results showed that the predicted area of high erosion intensity showed good consistency with the experimental area of erosion.…”
Section: Research On Wear Of Solid-liquid Two-phase Centrifugal Pumpmentioning
confidence: 99%
“…Wu et al [18] studied the influence of unstable flow characteristics on pump performance and found that relatively high-speed particles would accelerate blade tail wear. Shi et al [19] studied the internal flow field in a solid-liquid centrifugal pump and proposed the wear equation to predict the volute wear caused by solid-liquid two-phase flow. The experimental results showed that the predicted area of high erosion intensity showed good consistency with the experimental area of erosion.…”
Section: Research On Wear Of Solid-liquid Two-phase Centrifugal Pumpmentioning
confidence: 99%
“…Regardless of how the particle shape and wear mode change, the volute is the main wear part. Shi et al (Shi et al, 2020) performed a numerical study on the internal flow field of a solid-liquid centrifugal pump and used the wear equation to predict the wear of the volute casing due to the solid-liquid twophase flow. The wear mechanism of the volute casing of a centrifugal pump is analyzed in detail and systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [1] used a CFD-DEM coupling algorithm to study the spatial distribution and motion characteristics of particles with different sizes, and the effects of particle diameter on the intensity and scale of the vortex in a guide vane were investigated; it was concluded that the existence of particles had a limited effect on the hydraulic performance of the pump in low-concentration fluids. In a numerical study of the internal flow field of the solid-liquid slurry pump, Shi et al [2] analyzed the wear mechanism of the volute wall of a slurry pump and proposed an effective wear equation for estimating the wear strength and wear area of the slurry pump volute. Peng et al [3] analyzed slurry flow under different particle concentrations and volume flows by using the Euler-Euler method, and the effects of particle concentration on flow resistance, reflux, and wall wear were assessed.…”
Section: Introductionmentioning
confidence: 99%